HUBUNGAN KEMAMPUAN BERPIKIR KRITIS TERHADAP PRESTASI AKADEMIK MAHASISWA PROGRAM STUDI PENDIDIKAN IPS FKIP UNIVERSITAS TANJUNGPURA - Frederika Yolanda Devitania; Aminuyati; Venny Karolina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
ABSTRACT This study aims to determine and obtain data regarding the relationship between critical thinking skills and academic achievement in students of the Social Studies Education study program at Tanjungpura University. The method used is a quantitative approach in the form of Ex Post Facto. The population in this study were students of the Social Studies Education study program, FKIP, Tanjungpura University, class of 2022, 2023, and 2024, consisting of 104 students with a research sample of 83 students taken based on a non-probability sampling technique with a voluntary sampling type. Data collection in this study used a questionnaire. The data analysis technique used descriptive statistical analysis. The results of the study showed that there was no significant relationship between critical thinking skills and academic achievement, namely the sig. (2-tailed) value of 0.196 (p>0.05) and the correlation coefficient value of 0.143, which means that the relationship between critical thinking skills and academic achievement has a very low (very weak) correlation level even though it has a positive value (0.143). The conclusion of this study indicates that critical thinking skills are not the sole benchmark for achieving good academic achievement and can be caused by internal factors such as self-motivation and external factors such as the existence of digital literacy and artificial intelligence (AI) that provide convenience to individuals. Respondents' critical thinking skills are also not in line with GPA values ​​due to the tendency for students to easily obtain GPA scores and are one of the indicators for assessing the study program accreditation system to achieve the